Research Workforce Diversity: The Case of Balancing National versus International Postdocs in US Biomedical Research. (28th May 2013) - Ghaffarzadegan, Navid; Hawley, Joshua; Desai, Anand
<x xml:space="preserve">Abstract</x> The US government has been increasingly supporting postdoctoral training in biomedical sciences to develop the domestic research workforce. However, current trends suggest that mostly international researchers benefit from the funding, many of whom might leave the USA after training. In this paper, we describe a model used to analyse the flow of national versus international researchers into and out of postdoctoral training. We calibrate our model in the case of the USA and successfully replicate the data. We use the model to conduct simulation‐based analyses of effects of different policies on the diversity of postdoctoral researchers. Our model shows that capping the duration of postdoctoral careers, a policy proposed previously, favours international postdoctoral researchers. The analysis suggests that the leverage point to help the growth of domestic research workforce is in the pregraduate education area, and many policies implemented at the postgraduate level have minimal or unintended effects on diversity. Copyright © 2013 John Wiley & Sons, Ltd.